A Case Series of Cystinuric Stone Formers in Western Cape, South Africa: SLC3A1 or SLC7A9 Mutations and Phenotype - Lisa-Ann Kaestner; John Lazarus; Azola Salukazana; Elmi Muller; Karl-Heinz Jehle (Société Internationale d’Urologie Journal)
ObjectiveTo describe the genetic mutations and phenotype in the first African series of patients with cystinuria. MethodsPatients with cystinuria were recruited from a specialist metabolic renal stone clinic in Cape Town, South Africa, for DNA sequencing to detect mutations in SLC3A1 and SLC7A9. Chart reviews and patient interviews were conducted to record demographics, previous medical history, family history, stone-specific history, age at first presentation, cystinuria complications, urine cystine:creatinine ratio, stone analysis, and serum creatinine. ResultsNine patients were included: 3 male patients and 6 female patients. The mean age (± SD) of patients was 33.43 ± 19.96 years. The median age (± IQR) at initial diagnosis of cystinuria was 16 ± 18 years, but the age ranged from 2 to 66 years. Three of 9 patients included (33.3%) had chronic kidney disease (CKD); however, none were receiving dialysis. Most patients initially presented with a staghorn calculus (4/9; 44.4%). The mean serum creatinine (± SD) was 84 ± 38 μmol/L. The mean urine cystine (± SD) was 2083 ± 1249 nmoL/mg creatinine. Eight patients had mutations in the SLC3A1 gene; 1 had mutations in both SLC3A1 and SLC7A9. Of the patients with only SLC3A1 mutations, 1 patient was homozygous and the rest were compound heterozygotes (two different mutations identified in the same gene). Four patients had a pathogenic variant in addition to an “uncertain significance” variant in SLC3A1. There were 9 mutations (5 pathogenic and 4 “unknown significance”) in SLC3A1 and 1 mutation in SLC7A9. Two of these were novel mutations. ConclusionThis “first in Africa” series of cystinuria patients showed marked heterogeneity in both phenotype and genotype, with a predominance of SLC3A1 mutations. This heterogeneity is similar to that reported in international cohorts.